Knowledge Attitude and Practice of Young Adults’ Usage of Artificial Intelligence for Health Symptoms Search - Udo, Patience Ekemini; Okpongkpong, Grace Imaikop (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This study investigates the knowledge, attitudes, and practices (KAP) of young adults regarding the use of artificial intelligence (AI) for health symptom searches. As AI-powered tools like chatbots and symptom checkers become more prevalent, they offer convenient and immediate access to preliminary medical information, particularly appealing to digitally literate populations like university students. Using a quantitative survey design, data were collected from 400 undergraduate students at the University of Uyo, Nigeria. Findings indicate a high level of engagement with online health information, with most students reporting confidence in symptom identification and frequent use of the internet for health-related inquiries. However, a significant knowledge–attitude–practice gap was observed: while many students possessed basic health literacy and held positive attitudes toward AI’s potential, their practical use of AI for health purposes was limited, and they expressed considerable anxiety about the accuracy of online information. Trust remained highest in healthcare professionals over AI-generated advice. The study concludes that although young adults are proactive in using digital tools for health information, there is a critical need for enhanced digital health literacy programs to promote the safe, informed, and critical use of AI in health-seeking behaviors.